THE INFLUENCE OF SERVICE QUALITY ON CUSTOMER SATISFACTION IN THE TEENAGE KURING RESTAURANT SERPONG, SOUTH TANGERANG - Setiawan, Christin (Universitas Islam Lamongan, 2024)
This research aims to investigate the influence of service quality on customer satisfaction at the Teen Kuring Serpong Restaurant, South Tangerang. Service quality is measured along several dimensions, including staff friendliness, food quality, service speed, and environmental cleanliness. The survey method was used to collect data from restaurant customers. Statistical analysis was carried out to evaluate the relationship between service quality and customer satisfaction. The research results show that service quality significantly impacts customer satisfaction. Practical recommendations from this research can help restaurant management improve their services. This research contributes to understanding the factors influencing customer satisfaction in the restaurant industry. It is hoped that this research can provide valuable insights for stakeholders in the culinary industry to improve their customer experience and business performance.